1992
DOI: 10.1161/01.res.70.6.1217
|View full text |Cite
|
Sign up to set email alerts
|

Depression of peak force without altering calcium sensitivity by the superoxide anion in chemically skinned cardiac muscle of rat.

Abstract: Among the mechanisms postulated to contribute to myocardial "stunning" is a depression of contractility by oxygen-derived free radicals. It has been suggested that these radicals might depress the calcium sensitivity of the contractile proteins. We have exposed the myofilaments (in chemically "skinned" rat cardiac muscle) to the superoxide anion and measured isometric force at controlled degrees of activation. Superoxide was generated by the xanthine/xanthine oxidase system: the effects to be described were sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
36
0
2

Year Published

1994
1994
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(45 citation statements)
references
References 19 publications
7
36
0
2
Order By: Relevance
“…It has also been demonstrated that, while O 2 ⅐ Ϫ can depress maximum force, it has no apparent effect on the sensitivity of the contractile apparatus to Ca 2ϩ (4,39). Similar results were obtained on cardiac muscle where O 2 ⅐ Ϫ production decreased force but did not affect Ca 2ϩ sensitivity or SR function (21). On the basis of these findings, and the fact that, at or above 37°C, there is a marked loss in function of the isolated muscle (16), we hypothesized that the loss of skeletal muscle function at or above 37°C must be connected to the increase in the amount of O 2 ⅐ Ϫ produced by the mitochondria in the skeletal muscle fibers.…”
supporting
confidence: 84%
“…It has also been demonstrated that, while O 2 ⅐ Ϫ can depress maximum force, it has no apparent effect on the sensitivity of the contractile apparatus to Ca 2ϩ (4,39). Similar results were obtained on cardiac muscle where O 2 ⅐ Ϫ production decreased force but did not affect Ca 2ϩ sensitivity or SR function (21). On the basis of these findings, and the fact that, at or above 37°C, there is a marked loss in function of the isolated muscle (16), we hypothesized that the loss of skeletal muscle function at or above 37°C must be connected to the increase in the amount of O 2 ⅐ Ϫ produced by the mitochondria in the skeletal muscle fibers.…”
supporting
confidence: 84%
“…In spite of suggestions that SH oxidation of tropomyosin and/or actin in combination with myosin light chain1 (MLC1) (Hertelendi et al 2008) are potential mediators of oxidative myocardial contractile depression, it is currently difficult to clearly state that oxidation of myofilament proteins causes cardiac dysfunction, since studies have reported equivocal effects in different muscle types and even within a single muscle type. The role of oxidation of myofilament proteins in cardiac dysfunction in the heart is currently confused, as decreased Ca 2+ sensitivity has been reported (Posterino and Lamb 1996;Lamb and Posterino 2003;Hertelendi et al 2008) while others reported no changes or even increases in Ca 2+ sensitivity (MacFarlane and Miller 1992;MacFarlane and Miller 1994). Interestingly, slow twitch muscle differed from fast twitch muscle in relation to the addition of cysteine oxidants during muscle contraction (Lamb et al 1995;Lamb and Posterino 2003), suggesting that oxidative responses may be dependent on positions and differences between cysteines in fast and slow skeletal muscle.…”
Section: Impact Of Oxidative Stress On Cardiomyocyte Stiffness Sarcommentioning
confidence: 99%
“…1,3,7,9,10 Furthermore, altered myofilament responsiveness may be involved in OH-induced dysfunction. 11 The troponin complex may be a potential target, whereby radicals may interact directly with the molecules or initiate specific, possibly Ca 2ϩ -dependent, proteolytic pathways. 3,12,13 The relative contribution of these different subcellular defects to the development of acute myocardial dysfunction after OH exposure remains unresolved.…”
mentioning
confidence: 99%